THE EXPORT POTENTIAL OF THE AGRARIAN SECTOR OF UKRAINE IN A COMPETITIVE ENVIRONMENT - I. O. Kryukova; T. Ye. Kalyna; V. P. Рanteleiev; S. M. Minakova (Фінансово-кредитна діяльність: проблеми теорії та практики)
The purpose of the paper is to investigate the level of competitiveness of agricultural and food products and to identify the possible areas of export development on the basis of scientific works and the existing system of national strategy of the agricultural sector development. The concept of «export potential of the agricultural sector” and its relation to the competitiveness of agricultural enterprises was revealed. The dynamics and the geography of Ukrainian export of agro-food products was investigated. The data of the State Statistics Committee of Ukraine for 2005—2016, Internet resources, and own observations served as the basis for the research. For the purposes of the research such groups of the most important product types were selected: cereals, namely: winter wheat, winter barley, corn; vegetable oil (sunflower, rapeseed, soybean), strawberry, sunflower and soya, etc., and as well as those that at the present stage are advocated and, thus, may significantly raise export potential in the long term (meat, poultry, dairy products, etc.). Change in the orientation of agro-export is associated with several factors: firstly, difficult political relationships with the Russian Federation resulted in a significant reduction in the volumes of exports to this country; secondly, the increase in exports to EU countries in connection to the signing of association agreement with the EU; thirdly, the continued growth of exports to the countries of Asia and Africa.It is the «competitiveness» that identifies the opportunities for the products supply on external markets, and this is a potential set of types of agro-food products, which domestic agricultural enterprises are able to export, that identifies the potential of the agricultural sector. Ukrainian producers have the advantage over the competitors in terms of the quality and products prices which is confirmed by the fact that domestic products are exported to more than 90 countries of the world. The use of the model of potential growth of export potential of the Ukrainian agro-products will able to fully provide growers with information about potential markets for products, to ensure the proper support for the promotion of products on foreign markets.